2022
DOI: 10.1186/s12887-022-03346-7
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight influences differently on systolic and diastolic blood pressure in children and adolescents aged 8–15

Abstract: Aim Globally, hypertension is one of the main threats to public health and a significant risk factor predisposing individuals to various cardiovascular conditions. Hypertension in the young is particularly complex and challenging. Accumulating evidence has implicated that low birth weight is vital for elevated blood pressure, and birth weight was negatively correlated with blood pressure. However, fewer studies with conflicting results have addressed the associations between birth weight and bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Most studies of birthweight and child cardiovascular outcomes have focused on BP and have typically identified negative associations between birthweight and systolic BP, consistent with the Barker hypothesis [21,[24][25][26][27]68]. In our study, we observed no association between birthweight and BP among the overall sample, possibly due to the small number of children born SGA in our study sample or the timing of the cardiovascular measurements being too early to detect an effect of birthweight on BP.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Most studies of birthweight and child cardiovascular outcomes have focused on BP and have typically identified negative associations between birthweight and systolic BP, consistent with the Barker hypothesis [21,[24][25][26][27]68]. In our study, we observed no association between birthweight and BP among the overall sample, possibly due to the small number of children born SGA in our study sample or the timing of the cardiovascular measurements being too early to detect an effect of birthweight on BP.…”
Section: Discussionsupporting
confidence: 76%
“…He specifically identified a correlation between low birthweight and risk of poor future cardiovascular health in adulthood, including high BP and mortality from cardiovascular disease, which has been extensively replicated in more recent studies [13–18]. Although Barker explored the association between birthweight and cardiovascular disease in adulthood, fewer studies have investigated whether birthweight is linked to cardiovascular health in early childhood [19–28] and, among these, only a small number have collected measures beyond BP [19–21], an important step toward advancing understanding of the developmental origins of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Similar differences in the effect of a birth condition have been reported among adult preterm males (55) and females (56). An increased risk of systolic hypertension without any effect on diastolic blood pressure has been also reported among preterm individuals (57), with an increase in both systolic and diastolic blood pressure in the general adolescent population (58).…”
Section: Higher Blood Pressure Was Observed In Malesmentioning
confidence: 66%
“…Few studies have examined BP at the age of two years. Previous studies have mostly examined BP in school-age children and adolescents (age range 7–18 years), and their findings were inconsistent [ 32 , 33 , 34 ]. A cross-sectional study reported no association between birthweight and BP in adolescents (12–18 years) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study reported no association between birthweight and BP in adolescents (12–18 years) [ 32 ]. However, birthweight was also found to be negatively related to SBP [ 33 ] or to have a U-shaped relationship with the risk of hypertension in children and adolescents [ 34 ].…”
Section: Discussionmentioning
confidence: 99%